Regional emissions of soil greenhouse gases across Tibetan alpine grasslands - Wang, Peiyan; Wang, Jinsong; Elberling, Bo; Ambus, Per; Li, Yang; Pan, Junxiao; Zhang, Ruiyang; Guo, Hui; Niu, Shuli (Geoderma, 2024)
•Large spatial variations in soil CO2 and N2O emissions and CH4 uptake on QTP.•Soil pH, moisture, C/N availability, and fungi jointly control CO2 emission.•High soil pH limits N2O emission and pmoA abundance dominates CH4 uptake.•Temperature sensitivity of each soil greenhouse gas (GHG) emission varies across QTP.•Warming increases regional soil GHG balance of 17.6% (1.5℃), 24.8% (2℃), 38.9% (3℃) Soil greenhouse gas (GHG) emissions play an important role in regional climate feedback on the Qinghai-Tibetan Plateau (QTP). Previous studies have focused on soil GHGs based on observations within a limited space on the QTP, however, the regional GHG emissions remain unclear. Analyzing soil samples from 25 sites along a 2,700 km transect across QTP, we showed significantly higher soil CO2 and N2O emission rates in alpine meadows than other upland grassland types, but similar soil CH4 uptake rates across all grassland types. The spatial variations of total soil GHG balance were dominated by CO2 emission. We found that CO2 emission was primarily constrained by high soil pH, low soil moisture and nutrient availability, and fungal abundance, N2O emission was inhibited by high soil pH, while CH4 uptake was dominated by methanotrophic abundance. Furthermore, we estimated a current regional total soil GHG balance of 144.4 Tg CO2-eq yr−1 for surface soil across Tibetan alpine grasslands, which increased by 17.6%, 24.8%, and 38.9% under warming scenarios of 1.5℃, 2℃ and 3℃, respectively. Our results provide a baseline for regional soil GHG emissions responding to climate warming on the QTP.